Screening of Polyvalent Phage-Resistant Escherichia coli Strains Based on Phage Receptor Analysis - Li, Ping; Lin, Hong; Mi, Zhiqiang; Xing, Shaozhen; Tong, Yigang; Wang, Jingxue (Frontiers in Microbiology, 2019)
Bacteria-based biotechnology processes are constantly under threat from bacteriophage infection, with phage contamination being a non-neglectable problem for microbial fermentation. The essence of this problem is the complex co-evolutionary relationship between phages and bacteria. The development of phage control strategies requires further knowledge about phage-host interactions, while the widespread use of Escherichia coli strain BL21 (DE3) in biotechnological processes makes the study of phage receptors in this strain particularly important. Here, eight phages infecting E. coli BL21 (DE3) via different receptors were isolated and subsequently identified as members of the genera T4virus, Js98virus, Felix01virus, T1virus, and Rtpvirus. Phage receptors were identified by whole-genome sequencing of phage-resistant E. coli strains and sequence comparison with wild-type BL21 (DE3). Results showed that the receptors for the isolated phages, designated vB_EcoS_IME18, vB_EcoS_IME253, vB_EcoM_IME281, vB_EcoM_IME338, vB_EcoM_IME339, vB_EcoM_IME340, vB_EcoM_IME341, and vB_EcoS_IME347 were FhuA, FepA, OmpF, lipopolysaccharide, Tsx, OmpA, FadL, and YncD, respectively. A polyvalent phage-resistant BL21 (DE3)-derived strain, designated PR8, was then identified by screening with a phage cocktail consisting of the eight phages. Strain PR8 is resistant to 23 of 32 tested phages including Myoviridae and Siphoviridae phages. Strains BL21 (DE3) and PR8 showed similar expression levels of enhanced green fluorescent protein. Thus, PR8 may be used as a phage resistant strain for fermentation processes. The findings of this study contribute significantly to our knowledge of phage-host interactions and may help prevent phage contamination in fermentation.